Feature extraction method and neural network pattern recognition on time-resolved partial discharge signals - Tho N.T.N.; Chakrabarty C.K.; Siah Y.K.; Ghani A.B.Abd. (2023)
Magnetic sensor is a relatively new method to collect time-resolved partial discharge (PD) signals in XLPE cables. This paper proposes a simple yet effective method to recognize patterns of PD signals obtained from the magnetic sensor. The technique consists of wavelet transformation to de-noise the signals, statistical analysis to extract features and multi-layer perceptron back propagation (MLP BP) neural network to classify different types of PD signals. The result is elaborated in this paper. 2011 IEEE.